IMPLEMENTASI PEMBAYARAN NAFKAH ANAK PASCA PERCERAIAN DI KABUPATEN KUTAI TIMUR KALIMANTAN TIMUR - Hariyadi, Luqman; Darmawati; Salehudin (The Juris, 2023)
The purpose of this research is to understand and analyze the implementation of child support payments post-divorce in Kutai Timur Regency, East Kalimantan Province. The research method used is a field study with a normative-empirical approach. Primary data sources were gathered through interviews with the Chief of the Religious Court in Sangatta, judges, child support claimants, and other relevant parties. The results of this research indicate that child support payments after the dissolution of marriage in the jurisdiction of the Religious Court in Sangatta are still not functioning properly. This is due to the economic incapacity of the fathers and negligence on the part of fathers in providing post-divorce child support.